2021
DOI: 10.4049/jimmunol.206.supp.59.13
|View full text |Cite
|
Sign up to set email alerts
|

Probing the naturally acquired immune response to malaria for broadly reactive antibodies targeting P. falciparum antigens linked with severe disease

Abstract: Severe malaria is caused by the adhesion of Plasmodium falciparum-infected erythrocytes to host receptors on vascular endothelium. Specifically, binding of the parasite variant surface antigen domain CIDRa1 to host endothelial protein C receptor (EPCR) is strongly associated with severe disease. In malaria-endemic regions, children quickly develop immunity against severe malaria, indicative of the development of an effective immune response against CIDRa1 domains. Indeed, serum IgG from naturally immune indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Specifically, we showed that VH3-48 was overrepresented among IgG + atypical B cells. Interestingly, we have recently isolated two broadly inhibitory antibodies against CIDRα1 that both used VH3-48 (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we showed that VH3-48 was overrepresented among IgG + atypical B cells. Interestingly, we have recently isolated two broadly inhibitory antibodies against CIDRα1 that both used VH3-48 (20).…”
Section: Discussionmentioning
confidence: 99%
“…This panel included antigen tetramers that allowed for the detection of B cells with specificity to two classes of P. falciparum antigens: (i) merozoite proteins involved in erythrocyte invasion (merozoite surface protein 1 [MSP1] and apical membrane antigen 1 [AMA1]), and (ii) the cysteine-rich interdomain region α1 (CIDRα1) domain of the variant surface antigen P. falciparum erythrocyte membrane protein 1 (PfEMP1) that is expressed on the surface of the infected erythrocyte. These antigens were selected because we have previously used these proteins to isolate monoclonal antibodies with confirmed antigen specificities (10,20). To assess the composition of the B cell compartment irrespective of antigen-specificity, we first determined the relative abundance of major B cell populations during high P. falciparum transmission and after a reduction in parasite exposure.…”
Section: Activated B Cell Subsets Decrease In Abundance In the Absenc...mentioning
confidence: 99%